Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.addr.2017.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Bio-synthetic materials for immunomodulation of islet transplants

Abstract: Clinical islet transplantation is an effective therapy in restoring physiological glycemic control in type 1 diabetics. However, allogeneic islets derived from cadaveric sources elicit immune responses that result in acute and chronic islet destruction. To prevent immune destruction of islets, transplant recipients require lifelong delivery of immunosuppressive drugs, which are associated with debilitating side effects. Biomaterial-based strategies to eliminate the need for immunosuppressive drugs are an emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 82 publications
(87 reference statements)
0
18
0
Order By: Relevance
“…A high PEG concentration of 20% was used to fabricate the microporous hydrogel to improve mechanical robustness for potential clinical use, which may alter crosslinking density and thus substrate stiffness (DeForest and Anseth, 2012). However, isolated islets have been shown to survive and function on or within a wide range of polymeric biomaterial substrates with varying stiffness both in vitro and in vivo in numerous studies (Apeldoorn, 2015; Buitinga et al, 2013; Foster and García, 2017; Graham et al, 2013; Pedraza et al, 2013; Phelps et al, 2013; Smink et al, 2017).…”
Section: 5 Discussionmentioning
confidence: 99%
“…A high PEG concentration of 20% was used to fabricate the microporous hydrogel to improve mechanical robustness for potential clinical use, which may alter crosslinking density and thus substrate stiffness (DeForest and Anseth, 2012). However, isolated islets have been shown to survive and function on or within a wide range of polymeric biomaterial substrates with varying stiffness both in vitro and in vivo in numerous studies (Apeldoorn, 2015; Buitinga et al, 2013; Foster and García, 2017; Graham et al, 2013; Pedraza et al, 2013; Phelps et al, 2013; Smink et al, 2017).…”
Section: 5 Discussionmentioning
confidence: 99%
“…Poly(ethylene glycol) (PEG)-based gels, another commonly used encapsulation material, are less immunogenic, non-ionic polymers, and are stable at physiological conditions [181]. Variation in the molecular weight of the PEG polymer can be used to control protein adsorption and permeability of the membrane by adjusting the porosity [182].…”
Section: Islet Encapsulationmentioning
confidence: 99%
“…Materials which are used for encapsulation are also capable carriers for inhibitors of local inflammation [181]. The cytokine transforming growth factor-β (TGFβ) [198] and chemokine CXCL12 [199,200] have been locally delivered in encapsulation materials to suppress the inflammatory response.…”
Section: Islet Encapsulationmentioning
confidence: 99%
“…Such strategies include assembling a thin layered PEG-lipid structure around the surface of islets and assembling a multilayer film around islets using biotin and streptavidin [48]. It has been recently demonstrated that the simple PEGylation of islets provided modest immunoprotection in full MHC mismatched mice [42].…”
Section: Biomaterials In Transplantationmentioning
confidence: 99%